Accounting and Regulation New Insights on Governance, Markets and Institutions - Di Pietra, Roberto.; Di Pietra, Roberto.; McLeay, Stuart.; McLeay, Stuart.; Ronen, Joshua.; Ronen, Joshua. (Springer New York : Imprint: Springer, 2014)
Since 1998, the world’s leading experts on accounting and regulation have convened in a series of workshops to explore emerging issues in their field, and to analyze the social and economic consequences. The workshops have covered a wide array of topics, including international standard setting, corporate governance, auditing, financial disclosure, and the dynamics of markets and institutions. They have addressed some of the most significant developments in the international financial economy, including the role that accounting practices and policies may have played in the global financial crisis.   In this volume, the editors select contributions to the workshops that are representative of the full spectrum of issues debated, illustrating the negotiable nature of the current regulatory framework of accounting. By challenging standard theories, and also providing a wealth of new evidence, this volume includes outstanding examples of state-of-the-art research, with a strong emphasis on the implications for accounting practice and policymaking.